Desensibilización a pirfenidona. Caso Clínico - Bastías O, Carla; Reyes C, Felipe; Rodriguez M, Karla; Diaz B, Ilenee (Revista Médica de Chile, 2021)
We report a 68-year-old woman with a history of idiopathic pulmonary fibrosis, who had immediate skin reactions associated with the use of pirfenidone in two opportunities. In the evaluation by immunology, an allergy to pirfenidone was diagnosed. Given the urgent need for the drug, a desensitization procedure was started. The dose of the medication was increased progressively, previous premedication with cetirizine, ranitidine and montelukast. After this procedure the patient was able to tolerate the treatment with pirfenidone without cutaneous reactions.